Export Supply Response Capacity Constraints A focus on the Uganda’s Export Performance - Mwebaze, T.; Kavuma, S.; Hisali, E. (The African Economic Research Consortium, 2013)
Macroeconomic stability has been achieved for quite some time in Uganda where for the last decade the country has had a single digit inflation rate averaging at 5% and GDP growth rate of an average of 6% over the last decade (Statistical Abstracts, 2000-2008). Despite the progress at the macro level, the performance of exports has not been commensurate with the growth of the economy. Thus, with the sustained macroeconomic stability and growth, one would have expected a higher export performance, leading to a decline in the trade deficit. However, this has not been the case. The relatively low performance of Uganda’s exports has been mainly caused by poor performance in supply capacity, rather than a deterioration of the foreign markets. Whereas the macroeconomic policy environment has been favorable for investors in Uganda, other infrastructure related constraints, particularly utilities, remain a major challenge. It follows that the export behavior and performance of current exporters is an area of legitimate interest, and such studies can be of importance to both public and private sector administers concerned with future export development and success.